Lymphogranuloma venereum: an emerging problem in Poland - Smolarczyk, Katarzyna; Młynarczyk-Bonikowska, Beata; Majewski, Sławomir; Rudnicka, Ewa; Unemo, Magnus; Fiedor, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Lymphogranuloma venereum (LGV) is a sexually transmitted disease that increases in incidence, particularly in more developed countries worldwide. LGV is caused by Chlamydia trachomatis serovars/genovars L1-3, including their subvariants, and in Europe mostly affects men who have sex with men (MSM). It can be asymptomatic but has now emerged as a frequent cause of severe proctitis/proctocolitis, especially in MSM. LGV has often been misdiagnosed as C. trachomatis serovars/genovars D-K infection. It is essential with accurate diagnosis that ensures appropriate treatment and protects the patient from complications and sequelae as well as from the consequences of misdiagnosis, e.g. as inflammatory bowel disease or cancer. We present a systematic review of LGV and two new LGV cases diagnosed in Poland.